Pengaruh Influencer Marketing dan Content Marketing terhadap Keputusan Pembelian pada Aplikasi TikToK: Studi Kasus Pengguna Aktif Aplikasi Tiktok Gen Z di Kota Jambi - Galih Harfinaldi; Dahmiri Dahmiri; Husni Hasbullah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study analyzes the influence of influencer marketing and content marketing on the purchasing decisions of active TikTok users from Generation Z in the city of Jambi. Using a quantitative method involving 96 respondents and PLS analysis, the results show that both variables have a positive and significant effect on purchasing decisions. Influencer credibility such as the expertise, authenticity, and reputation they demonstrate and the quality of content that is engaging, informative, relevant, and delivered consistently have been proven to increase consumer interest and trust in purchasing products through the TikTok platform. In addition, the presence of interactive features such as comments, likes, live streaming, and algorithm-based recommendation systems further strengthens user engagement, making promotional messages more easily accepted and processed by Generation Z, who are known to be highly responsive to visual and digital stimuli. These findings emphasize the importance of influencer-based digital marketing strategies and creative content in influencing purchasing behavior, while also highlighting the need for brands to adapt to the rapidly evolving nature of social media trends in order to reach their target audience effectively and maintain competitiveness in today’s modern marketing environment.